Processing considerations and improved interpretation for ground‐penetrating radar imaging of a relict archaeological excavation unit. Issue 4 (27th July 2018) - Lanzarone, Peter; Bigman, Daniel
ABSTRACT: A ground‐penetrating radar survey was carried out at The Great Temple Mound (Mound A), Ocmulgee National Monument, Georgia, USA to determine the location of buried archaeological features. Mound A is the largest pre‐historic mound at the site and its function remains unclear. High quality data and sufficient spatial sampling with a 500‐MHz centre frequency antenna facilitated the generation of two‐dimensional profiles and amplitude depth slices. The analyses presented here describe a processing sequence used to improve the image fidelity and the visualization of the remains of a relict archaeological excavation unit. Additionally, we employ depth slice overlay analysis for enhanced visualization of this feature. The results demonstrate a new processing methodology that helps in delineating the lateral extent of the excavation and its evolution. The results also highlight the implementation of a new visualization strategy in GPR surveys aimed towards detecting graves, burial tombs, and other rectilinear or cubic features. We conclude that even with excellent GPR imaging, there may be significant positioning errors in defining the boundaries of buried features.